Comparative Performance Analysis of Monocrystalline and Polycrystalline 50 WP Solar Panels at Varying Solar Radiation Intensities During the Rainy Season - Fikih Fidulloh Gimasyah; Muhammad Kusban (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to analyze and compare the performance of monocrystalline and polycrystalline 50 Wp solar panels under varying solar radiation intensity conditions during the rainy season in Surakarta City. Methodology: A field experimental method was used, installing both panels side by side with identical orientation and tilt angles. Measurements were taken every hour from 07:00 to 17:00 WIB for seven days using an INA219 sensor-based data logger connected to an Arduino Uno microcontroller with SD card storage. Main Findings: Polycrystalline panels consistently produced higher power output than monocrystalline under low-to-medium irradiance conditions typical of the rainy season, with peak power of 41.323 W versus 39.338 W. Daily peak power fluctuated dramatically from 41.323 W (sunny) to 8.433 W (heavy overcast). Monocrystalline panels showed superior response during morning irradiance transition hours. Novelty/Originality of this study: This study provides empirical comparative data on both panel types specifically during the Indonesian tropical rainy season in Surakarta, offering practical design recommendations for PLTS systems in high-rainfall tropical regions, including a minimum 75-80% derating factor during rainy season.